A puzzle solved after two decades: SN 2002gh among the brightest of superluminous supernovae. Issue 2 (19th May 2022) - Cartier, Régis; Hamuy, Mario; Contreras, Carlos; Anderson, Joseph P; Phillips, Mark M; Morrell, Nidia; Stritzinger, Maximilian D; Hueichapan, Emilio D; Clocchiatti, Alejandro; Roth, Miguel; Thomas-Osip, Joanna; González, Luis E
ABSTRACT: We present optical photometry and spectroscopy of the superluminous SN 2002gh from maximum light to +204 d, obtained as part of the Carnegie Type II Supernova (CATS) project. SN 2002gh is among the most luminous discovered supernovae ever, yet it remained unnoticed for nearly two decades. Using Dark Energy Camera archival images we identify the potential supernova (SN) host galaxy as a faint dwarf galaxy, presumably having low metallicity, and in an apparent merging process with other nearby dwarf galaxies. We show that SN 2002gh is among the brightest hydrogen-poor SLSNe with MV  = −22.40 ± 0.02, with an estimated peak bolometric luminosity of 2.6 ± 0.1 × 10 44 erg s −1 . We discount the decay of radioactive nickel as the main SN power mechanism, and assuming that the SN is powered by the spin-down of a magnetar we obtain two alternative solutions. The first case, is characterized by significant magnetar power leakage, and M ej between 0.6 and 3.2 M⊙, P spin  = 3.2 ms, and B  = 5 × 10 13  G. The second case does not require power leakage, resulting in a huge ejecta mass of about 30 M⊙, a fast spin period of P spin ∼ 1 ms, and B ∼ 1.6 × 10 14  G. We estimate a zero-age main-sequence mass between 14 and 25 M⊙ for the first case and of about 135 M⊙ for the second case. The latter case would place the SN progenitor among the most massive stars observed to explode as an SN.